Utilization of Frying Water to Increase Phenolic and Flavonoid Content in Brassica Vegetables As Antioxidant Agents for The Body - Dilla Ambar Dewi; Salsabila Mahia Nadia; Saryono Saryono (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Background: Brassica vegetables are a type of vegetable that is easy to find and widely consumed by people in Indonesia because of their high variety and relatively cheap prices. Brassica vegetables such as cauliflower, broccoli, kale, and sprouts have a high antioxidant content due to their phenolic compounds. In general, Brassica vegetables are not consumed raw but through processing. The antioxidant compounds contained in brassica can be known depending on the processing method used. Various processing methods, one of which is the processing method using Air Frying. Objective: The purpose of this Systematic Review study was to examine the use of Air Frying in Brassica vegetables to increase the content of phenolic compounds and flavonoids. Method: The design used in this study is a systematic literature review (SLR) using the preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) method by searching journals in electronic databases published on Google Scholar, Pubmed, and Science Direct, which have been published since from 2013 to 2023. These articles were then extracted by paying attention to the titles and abstracts to see their suitability for the topics discussed. Results: The 5 selected articles show that hot air frying technology makes the nutritional quality of food higher than conventional frying, and becomes a practical alternative for getting healthier fried foods because of the possibility of reducing fat, lipid degradation, and oxidation. Air frying is becoming a more suitable processing method for processing brassica vegetables. Frying with high-temperature air for a short time will prevent the nutritional content of vegetables during processing. Air fryers are capable of significantly increasing the TFC and TPC of brassica vegetables regardless of the variety. Conclusion: The application of Air Frying improves the phenolic and flavonoid status and antioxidant potential of selected Brassica Vegetables.